Proceedings of the Twenty-Fifth Annual ACM Symposium on Principles of Distributed Computing 2006
DOI: 10.1145/1146381.1146411
|View full text |Cite
|
Sign up to set email alerts
|

Object location using path separators

Abstract: We study a novel separator property called k-path separable. Roughly speaking, a k-path separable graph can be recursively separated into smaller components by sequentially removing k shortest paths. Our main result is that every minor free weighted graph is k-path separable. We then show that k-path separable graphs can be used to solve several object location problems: (1) a small-worldization with an average poly-logarithmic number of hops; (2) an (1 + ε)-approximate distance labeling scheme with O(log n) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
175
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(178 citation statements)
references
References 42 publications
(45 reference statements)
3
175
0
Order By: Relevance
“…Thorup [Tho04] proves that any planar graph can be recursively separated by three shortest paths. Abraham and Gavoille [AG06] extend his result to minor-closed families, proving that any minor-free graph can be recursively separated by O(1) shortest paths. Since bounded-genus graphs exclude minors, we could use their result to obtain a linear-space distance oracle.…”
Section: Forward(g B P )mentioning
confidence: 89%
See 2 more Smart Citations
“…Thorup [Tho04] proves that any planar graph can be recursively separated by three shortest paths. Abraham and Gavoille [AG06] extend his result to minor-closed families, proving that any minor-free graph can be recursively separated by O(1) shortest paths. Since bounded-genus graphs exclude minors, we could use their result to obtain a linear-space distance oracle.…”
Section: Forward(g B P )mentioning
confidence: 89%
“…Since bounded-genus graphs exclude minors, we could use their result to obtain a linear-space distance oracle. The constant in [AG06] however depends on the size of the minor in an unspecified way. In the following, we prove that genus g graphs can be recursively separated using at most O(g) shortest paths.…”
Section: Forward(g B P )mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be distinguished two main kinds of augmentation processes in the navigable networks literature. One kind of augmentation relies on the graph density and its similarity with a mesh (like augmentations in [7,17,18,22]), while the other kind relies on the existence of good separators in the graph (like augmentations in [4,10]). Augmentation via embedding cannot be directly extended to augmentations using separators because of the difficulty to handle the distortion in the analysis of greedy routing.…”
Section: Discussionmentioning
confidence: 99%
“…where, for any node u and radius r ≥ 1, the 2r-neighborhood of u is of size at most a constant times its r-neighborhood. Fraigniaud [10] demonstrates that any bounded treewidth graph can also be augmented by one link per node to become navigable, and Abraham and Gavoille [4] showed that, more generally, this is possible for all graphs excluding a fixed minor. The definition of the problem can directly be extended to metric spaces by asking which n-points metric spaces 1 M = (V, δ) can be augmented by O(log n) links such that, in the resulting graph, greedy routing computes polylog(n) routes between any pair with the only knowledge of M .…”
Section: Introductionmentioning
confidence: 99%